Application of Ionophores in Cattle Diets - Matt Hersom; Todd Thrift (EDIS)
Beef cattle producers should consider using ionophores to increase calf gain and gain efficiency in a cost-effective manner. Ionophores are feed additives used in cattle diets to increase feed efficiency and body weight gain. They are compounds that alter rumen fermentation patterns. Ionophores can be fed to any class of cattle and can be used in any segment of the beef cattle industry. Similar to many other feed additives, ionophores are fed in very small amounts and supplied via another feedstuff as carrier for intake. Ionophores decrease incidence of coccidiosis, bloat, and acidosis in cattle. This 4-page fact sheet was written by Matt Hersom and Todd Thrift, and published by the UF Department of Animal Sciences, December 2012.